Dipping Pattern and 1-year stroke functional outcome in ischemic stroke or transient ischemic attack - Xia Ding; Yilun Zhou; Yuesong Pan; Jie Xu; Hongyi Yan; Xingquan Zhao; Yilong Wang; Yongjun Wang (Clinical and Experimental Hypertension, 2023)
Aims This study aimed to explore whether a relationship exists between dipping patterns and 1-year functional outcome in patients with acute ischemic stroke (IS) or transient ischemic attack (TIA). Methods Data from the Blood Pressure and Clinical Outcome in TIA or Ischemic Stroke Study (BOSS), a nationwide, hospital-based, longitudinal cohort study, was used for this study. Patients with acute IS or TIA were recruited within 7 days after onset and ambulatory blood pressure monitoring was performed during hospitalization. Patients were defined as dippers if nocturnal systolic blood pressure fell by ≥10%, non-dippers if 0–10%, and reverse dippers if < 0%. Poor functional outcome was defined as a modified Rankin Scale (mRS) score of 3–5. Logistic regression analysis was used to test the association between dipping patterns and 1-year functional outcome. Results Among the 1808 IS/TIA patients, 19.19% were dippers, 53.21% were non-dippers, and 27.60% were reverse dippers. Poor functional outcome occurred in 22.44% of reverse dippers, which was significantly higher than that of dippers (16.14%) and non-dippers (16.53%) (P = .014). A univariate analysis revealed that reverse dipping was a risk factor for poor functional outcome (Odds ratio 1.504, 95% confidence interval 1.055–2.145, P = .024). However, this significance disappeared after adjusting for confounders. Conclusions Reverse dipping was prevalent in patients with IS/TIA. The higher incidence of 1-year poor functional outcome in reverse dippers warrants further investigation.